Clinico-microbiological study of diabetic limb amputations in a tertiary care hospital in North India - Rajpal Singh Punia (Endocrinology Research Centre, 2015)
The diabetic population faces 80% increased risk of cellulitis, 4-fold increased risk of osteomyelitis and 2-fold risk of both sepsis and death caused by infections.Study objectives. The present study was carried out to assess the clinical aspects and microbiological profile of organisms isolated from 25 patients undergoing diabetic limb amputations.Materials and Methods. In 25 diabetes persons who underwent limb amputation, grading of ulcers was done according to Wagner system. Material was stained with Gram stain. Potassium hydroxide wet mounts were also studied. Culture was done in blood agar, MacConkey agar, Sabouraud dextrose agar tube slants and brain heart infusion broth and examined for growth. The histopathology sections were also studied and special stains were done.Results. Of 25 cases, 16 were males and 9 were females. The age ranged from 30 to 90 years (mean: 58?10.91). Majority of ulcers were grade 3. Osteomyelitis was seen in 13 (52%) cases; acute in 2 (8%), chronic in 3 (12%) and acute exacerbation of chronic osteomyelitis in 8 (32%) cases. On culture Proteus mirabilis was isolated in majority of cases followed by Escherichia coli. In 20 cases more than one bacterium were isolated. Candida was cultured in 8 cases followed by Trichosporon in 2 and Fusarium in one case. On histopathology Candida was seen in 3 cases, while one case showed spores of Trichosporon. 80% cases with osteomyelitis had polymicrobial infection.Conclusions. The isolation of etiologic agent helps in administering appropriate antibiotic regimens, thus reducing the problem of multidrug resistance, morbidity and surgical limb amputations in patients suffering from diabetes mellitus.